Perancangan Portable Continuous Passive Motion (CPM) sebagai Alat Bantu Rehabilitasi Fraktur Lutut Pasca Operasi Berbasis Internet of Things (IoT) - Nugroho, Warsat Resti Arbi; Hidayah, Syaiful Ari Hangga; Widodo, Rizki Nugraheni Budi; Saputri, Adila Eka; Prambudi, Fatkurohman Nanda; Riyanto, Ifnu Agus; Kusuma, I Wayan Angga Wijaya (Elektrika, 2022)
One of the steps needed in patients with fractures of the knee joint is therapeutic exercises guided by physiotherapists. Therapeutic exercise is a physiotherapy modality by moving the joints both actively and passively. Inspired by this, the Portable Continuous Passive Motion (CPM) tool was created which is a physiotherapy aid for patients after surgery or knee surgery. Portable Continuous Passive Motion (CPM) has been developed based on IoT. Portable Continuous Passive Motion (CPM) uses Arduino LoRa as a micro controller, a stepper motor as a driver and uses a software application as a controller. The form of this research is research and development. From the results of the development, it can be concluded that Portable Continuous Passive Motion (CPM) can be useful for postoperative fracture patients as a practical and flexible postoperative manual therapy tool.